A Tale of Two Surveys: Household Debt and Financial Constraints in Australia - Simon, J; La Cava, Gianni (My University, 2003)
Over the past decade, household debt (as a share of household income) has reached historically high levels. This has raised concerns about whether, as a result of the rise in debt, households are now more financially ‘fragile’. Using data from the 1998/99 Household Expenditure Survey (HES), a logit model is constructed to examine the relationship between the probability of being financially constrained and the economic and demographic characteristics of households in Australia. We find that the probability of a household being constrained is significantly affected by demographic and economic variables such as age, marital status, home ownership, weekly household income, the proportion of income earned from interest, and the share of income going to repayments on mortgage debt. Unfortunately, however, we cannot separately identify households with investor housing debt and so cannot examine the relationship between this component of household debt and the probability of being financially constrained. We also apply the model to data from the 1993/94 HES and the 2001 Household, Income and Labour Dynamics in Australia (HILDA) Survey. Our results imply that the overall proportion of households who are financially constrained in the economy has fallen or, at worst, remained unchanged between 1994 and 2001. Separating households into financially constrained and unconstrained groups, we find that much of the rise in debt appears to have been due to unconstrained households taking on more debt. As such, the rise in the aggregate debt to income ratio associated with owner-occupier mortgages appears to be the result of voluntary household choice rather than a result of increased household financial distress. Hence, the increase in owner-occupier mortgage debt has not been associated with an increase in the proportion of households who are financially constrained.
Reserve Bank of Australia Research Discussion Paper, RDP
Keywords: Finance -- Debt; Finance -- Expenditure and constraints on expenditure; Finance; Income, wealth and finances; Income, wealth and finances